Antioxidant, antibacterial, antitumor, antifungal, antiviral, anti-inflammatory, and nevro-protective activity of Ganoderma lucidum: An overview - Cör Andrejč, Darija; Knez, Željko; Knez Marevci, Maša (Frontiers in Pharmacology, 2022)
Ganoderma lucidum is a very medicinal mushroom that has been utilized in Oriental medicine for many years. It has a wide range of pharmacological and therapeutic properties, and has been used for many years as a health promoter. It contains various biologically active compounds that improve the immune system and have antioxidant, antitumor, anti-inflammatory, antifungal, and antimicrobial properties. Active compounds include triterpenoids and polysaccharides, as well as proteins, lipids, phenolics, sterols, etc. In the following review, we summarize briefly their biological activities, such as antioxidant, anti-bacterial, anti-fungal, antitumor, anti-viral, and anti-inflammatory activity. Although Ganoderma has a number of medicinal effects that have been confirmed by the in vitro and in vivo studies summarised in this review, there are some limitations. Clinical trials face mainly a lack of pure constituents. Accurate identification of the compounds obtained is also problematic. In addition, most of the included studies were small, and there were concerns about the methodological quality of each study. Studies have shown that Ganoderma has valuable potential for the prevention and treatment of cancer. In any case, G. lucidum cannot be used as first-line therapy for cancer.